(untitled) (The Strategic Review for Southern Africa, 2020)
This article explores the relations between the African Union and its member states. While there are improvements on the AU level with regard to the implementation of the African Peace and Security Architecture and the building of other institutions such as the Pan-African Parliament, it becomes apparent at the same time that on the state level governments are reluctant to engage in a deepening of the continental integration. Some countries even topple the integration process or undermine their own initiatives such as the African Peer Review Mechanism. This article examines this phenomenon, and labels the identified unwillingness to change the status quo a 'culture of conservatism'. Four explanations are offered for such a 'culture of conservatism': lack of capacity, unwillingness to surrender sovereignty, national leaders' reluctance to cede power, and the greater importance of regional economic communities as compared to the AU.